Databases as a Source Home Health Services for BINASSS - Siles, Virginia (1992)
Nowadays, with the technological advances in the field of communication and the information industry, it has become possible that all the published knowledge can be disseminated by different means among which we can cite books, periodical publications, abstract journals or indexes and databases. It is for this reason that an idea of systematization arises with the purpose of being able to offer to the user mechanisms that allow him to acquire the information in an agile form.